Personalized management of hypertensive patients: focus on prognostic biomarkers - S. V. Lyamina; S. V. Kalish; N. P. Lyamina (Российский кардиологический журнал)
Aim. To analyze level of circulating biomarkers of plasma vascular endothelial growth factor (VEGF) and tumor necrosis factor-α (TNF-α) during 3-month therapy with a fixed-dose combination of ramipril/indapamide (Konsilar-D24, AO Vertex, Russia), as well as to evaluate the antihypertensive efficacy of a fixed-dose combination of ramipril/indapamide (Konsilar-D24, JSC “Vertex”, Russia) in hypertensive (HTN) patients with type 2 diabetes (T2D).Material and methods. This prospective open-label study included 44 patients (aged 35 to 60 years) of both sexes with essential grade 1-2 HTN and concomitant compensated T2D, who did not reach the target blood pressure (BP) level using single or dual antihypertensive therapy, as well as patients who did not take antihypertensives. All patients included in the study initially underwent a set of standard clinical, laboratory and functional examinations in accordance with the clinical guidelines for the management of patients with HTN and T2D, as well as an assessment of the level of C-reactive protein, VEGF and TNF-α. Patients were monitored and treated with Konsilar-D24 for 3 months.Results. In 93,2% of patients, individual target BP values were achieved during the first 2-4 weeks of therapy with a fixed combination of ramipril/indapamide (Konsilar-D24). In the subsequent 3-month follow-up, the average daily BP level in all patients ranged from 129/79 mm Hg to 110/70 mm Hg. Three-month Konsilar-D24 therapy showed a decrease in microalbuminuria: the median values of microalbuminuria decreased by 2 times, and the decrease in the maximum recorded values reached 40% of the baseline. Decrease in mean TNF-α values after 3-month therapy with Konsilar-D24 was 33% of the baseline values, while the maximum recorded values during the specified period decreased by 17%. Decrease in median VEGF values after 3-month Konsilar-D24 therapy was 28%, while the maximum value decreased by 7%, the minimum — by 8%.Conclusion. Konsilar-D24 improves the prognosis in hypertensive patients not only by reducing BP to target values, but also by reducing the level of VEGF and TNF-α biomarkers that determine the progression of endothelial dysfunction, diabetic retinopathy, and microalbuminuria.